183k views
1 vote

x \: varies \: as \: product \: u \: v \: and \: inversely \\ as \: their \: sum \: if \: x - 3 \: when \: u = 3 \: \\ and \: v = 1 \: what \: is \: the \: value \: of \: x \: if \\ u = 3 \: and \: v = 3

Pls help me with this​

User Bwt
by
4.6k points

1 Answer

4 votes

[Note that you don't have to evaluate k to solve the problem]


x = (kuv)/((u+v))

That means that


x ((u+v))/((uv)) = k, a \: constant

So, you want
xsuch that


x ((3+3))/((3 * 3)) = 3 ((3+1))/((3 * 1))


x=6

User Anukul Limpanasil
by
5.2k points